THE DYNAMICS OF INTERACTION OF CULTURAL, ECONOMIC, AND SOCIAL FACTORS IN SHAPING FINANCIAL FINANCING PREFERENCES AND ENTREPRENEURIAL INTENTIONS OF FEMALE STUDENTS - Zeze Zakaria Hamzah; Mujito Mujito; Dadang Junaedi; Vionita Qatrunnada (PT. Jurnal Center Indonesia Publisher, 2026)
This study aims to analyze the influence of cultural, economic, and social factors on financial financing preferences and their implications for the entrepreneurial intentions of female students. Entrepreneurial intention refers to an individual's psychological readiness and commitment to start a business in the future. This research employs a quantitative approach using a survey method by distributing questionnaires to female students as respondents. Data analysis was conducted using Structural Equation Modeling (SEM) with the AMOS program to examine the relationships among the research variables. The results indicate that social factors have the most dominant influence on financial financing preferences and entrepreneurial intentions of female students. Cultural and economic factors also show positive effects on entrepreneurial intentions, although their influence is relatively smaller than social factors. In addition, financial financing preferences also contribute to shaping students’ entrepreneurial intentions. The findings of this study are expected to contribute to the development of entrepreneurship education in higher education institutions and encourage female students to pursue entrepreneurial activities.